Farmers’ Attitude towards Unfair Trade Practices in the Marketing of Grain Crops at Aurangabad District of Bihar - Mehta, Piyush; Kumar, Prabhat; Raina, Krishan Kumar; Thakur, Pankaj; Thakur, Ashok K. (International Journal of Economic Plants, 2021)
The concerned research is on studying the unfair trade practices that occur in the district of Aurangabad, Bihar with the objective to study the awareness level of grain farmers towards prevalent unfair trade practices in the marketing of grain crops, farmers attitude towards unfair trade practices and cartelization in the marketing of grain crops in reference to demographic and economic status of the farmers, to analyse the effectiveness of initiatives undertaken by government marketing authorities to control unfair marketing activities and to seek the farmer’s suggestive opinion on improving the marketing practices for grain. The primary data was obtained from the traders in the Aurangabad district of Bihar to fulfil these objectives. Traders are frequently subjected by the Arhatiyas to unfair trade practices and become a prey to their business competition that is cutting their throats. Throughout today’s modernized environment, trader’s consciousness gives way to fight against it and to evaluate the protection they are given against unfair trade activity. In our country, the prospect of the trader’s justice system seems bright in view of the provisions available in Indian statutes and legislation and various proactive policies, schemes being adopted by the Government. The illiterate group of traders should be made aware of their rights which monopolists can use to protect themselves from such unfair practices. In order to curb unfair trading practices, government should play an active role in it, trade openness, bringing high rate of APMC operating performance, increasing knowledge among farmers, providing correct information, developing better marketing network for Agricultural commodities export operations.